Intercultural musicking: learning through klezmer. (4th March 2022) - Fay, Richard; Mawson, Daniel J.; Bithell, Caroline
ABSTRACT: This article focuses on a particular arena of creative practice: music students' largely sonic experience of Otherness through world music ensemble performance of klezmer (music with its roots in the weddings and other social occasions of mostly Yiddish-speaking Ashkenazi Jews in eastern and central Europe). Having briefly introduced klezmer, we situate our university ensemble into the traditions for teaching/learning it. We then present our pedagogic framework which combines ethnomusicological and intercultural thinking. We conclude with observations on how the module enables both increased transmusicality (through experience of a musical Other) and increased intercultural awareness (through the cultural encounters generated through klezmer performance).